2023
DOI: 10.1371/journal.ppat.1011543
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR screen identifies genes synthetically lethal with GRA17, a nutrient channel encoding gene in Toxoplasma

Abstract: Toxoplasma gondii is a parasite that replicates within a specialized compartment called the parasitophorous vacuole (PV), which is surrounded by the PV membrane (PVM). To obtain essential nutrients, Toxoplasma must transport molecules across the PVM, a process mediated by the secreted parasite proteins GRA17 and GRA23. These proteins form pores in the PVM through which small molecules can diffuse in and out of the PV. GRA17 and GRA23 are synthetically lethal, suggesting that at least one pore type is essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 57 publications
3
25
0
Order By: Relevance
“…Despite much effort from the research community, many apicomplexan proteins still need to be annotated owing to their uniqueness and absence in other model organisms. The CRISPR screens enabled the researchers to investigate hundreds to thousands of genes in Toxoplasma at once in vitro culture or in vivo infection to identify essential genes for parasite growth, metabolism, drug resistance, differentiation, host-pathogen interaction, and virulence (10)(11)(12)(13)(14)(15)(25)(26)(27)(28)(29)(30)(31)(32)(33). Most in vivo CRISPR screens in Toxoplasma have been focused on identifying secreted virulence effectors such as rhoptry bulb proteins (ROPs) and dense granule proteins (GRAs) (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Despite much effort from the research community, many apicomplexan proteins still need to be annotated owing to their uniqueness and absence in other model organisms. The CRISPR screens enabled the researchers to investigate hundreds to thousands of genes in Toxoplasma at once in vitro culture or in vivo infection to identify essential genes for parasite growth, metabolism, drug resistance, differentiation, host-pathogen interaction, and virulence (10)(11)(12)(13)(14)(15)(25)(26)(27)(28)(29)(30)(31)(32)(33). Most in vivo CRISPR screens in Toxoplasma have been focused on identifying secreted virulence effectors such as rhoptry bulb proteins (ROPs) and dense granule proteins (GRAs) (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…S2). Endotagging, knockout generation and complementation of GRA72 has been described previously (7).…”
Section: Generation Of Parasite Strainsmentioning
confidence: 99%
“…To uncover additional genes encoding for proteins involved in nutrient acquisition from the host at the PVM, or the correct trafficking to and insertion into the PVM, in the absence of GRA17, we recently conducted a genome-wide synthetic lethality screen within a parasite background lacking GRA17 (7). This screen discovered multiple GRA proteins (GRA57, GRA70, GRA71, GRA72) that are required for the correct localization of GRA17/GRA23 to the PVM (7,8) while other studies have identified that GRA42, GRA43, and the chaperone-like GRA45 protein are also involved in this process (8,9). GRA72 was confirmed to be synthetically lethal with GRA17 and deletion of GRA72 in a wild-type background resulted in the formation of 'bubble' vacuoles with reduced permeability similar to GRA17 knockout parasites (7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations